2015
DOI: 10.1080/10286020.2014.1003183
|View full text |Cite
|
Sign up to set email alerts
|

FLZ attenuates learning and memory deficits via suppressing neuroinflammation induced by LPS in mice

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder in which neuroinflammation plays an important role. FLZ is a novel synthetic derivative of natural squamosamide. Previous studies demonstrated that FLZ had neuroprotective effects on AD models and showed strong anti-inflammatory property in Parkinson's disease models. However, whether the neuroprotective effects of FLZ on AD are associated with its anti-inflammatory property is still not fully elucidated. In this study, we aimed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The hope is to get satisfactory results from clinical studies with compounds that have been successful in vitro, ex vivo, and/or in vivo experiments, such as the administration of molecules like acetylpuerarin,138 edaravone,139 palmitoylethanolamide,38 N -[2-(4-hydroxyphenyl)ethyl]-2-(2,5-dimethoxyphenyl)-3-(3-methoxy-4-hydroxyphenyl) acrylamide (compound FLZ),140 oleuropeinaglycone,141 oridonin,142 protocatechuic acid,143 resveratrol,110 rutin,144 or immunotherapies145,146 and vaccinations 147…”
Section: Future Research Directionmentioning
confidence: 99%
“…The hope is to get satisfactory results from clinical studies with compounds that have been successful in vitro, ex vivo, and/or in vivo experiments, such as the administration of molecules like acetylpuerarin,138 edaravone,139 palmitoylethanolamide,38 N -[2-(4-hydroxyphenyl)ethyl]-2-(2,5-dimethoxyphenyl)-3-(3-methoxy-4-hydroxyphenyl) acrylamide (compound FLZ),140 oleuropeinaglycone,141 oridonin,142 protocatechuic acid,143 resveratrol,110 rutin,144 or immunotherapies145,146 and vaccinations 147…”
Section: Future Research Directionmentioning
confidence: 99%
“…It has been well documented that peripherally injected LPS induce a variety of central effects. Multiple injections of LPS increase the number of F4/80+, CD11b+, or Iba1-+ cells and induce morphological changes characteristic of activated microglia in the CNS [31] , [36] , [41] , [42] . We observed that the mice induced neuroinflammation and treated with GA-1 or GA-2 exhibited reduced Iba1+ microglial cells and GFAP+ astroglial cells in the hippocampus as compared with that in the hippocampus of mice treated with CP or left untreated ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Any perturbation of this balance that leads to more severe and persistent neuroinflammatory cycle could promote neurodegeneration culminating in clinical disease. Central or systemic LPS administration has been shown to increase the number of glial cells, upregulate proinflammatory cytokines in the brain, and eventually precipitate dopaminergic neurotoxicity [13,22,41,49]. Culture medium of LPS‐stimulated microglia cells enhanced NF‐κB p65 signaling and downregulated Bcl‐2 expression in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated nitric oxide (NO) released by astrocytes and microglia during neurodegenerative disease is both necessary and sufficient to induce primary microglial phagocytosis of neurons and leads to neurotoxic effects resulting from perturbed mitochondrial respiration [6][7][8] . Down-regulation of inducible nitric oxide synthase (iNOS) in AD-model mice, and subsequent decrease in NO, has been associated with rescue of cognitive function, reduction in Ab and NFT load, decreased glial activation, and attenuated neuronal loss [9][10][11] . As dysregulated activation of microglia resulting from inflammatory insult has been closely associated with AD brain regions exhibiting extensive deterioration, Ab deposition, and markers of NO-mediated protein damage [8,12,13] , it has been suggested that reducing microglial activation may be an effective means of treating neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%